Analysis of Related Factors on the Deformity Correction of Balloon Kyphoplasty - Xu, C. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: Balloon kyphoplasty is a minimally invasive surgical approach for treating vertebral compression fractures, including osteoporotic vertebral compression fractures. The purpose of this study was to determine the effect of balloon inflation and postural reduction on balloon kyphoplasty for the deformity correction of vertebral compression fractures and to explore the correlative factors affecting the deformity correction. MATERIALS AND METHODS: A retrospective study of 72 patients (75 levels) who had undergone balloon kyphoplasty was conducted. Imaging data and clinical features were collected and analyzed. Independent-samples t test analysis was used to find the possible factors affecting deformity correction. RESULTS: Postural correction in the overextending position significantly increased anterior middle vertebral height, kyphotic angle, and Cobb angle (each P < .05). There was no significant difference in anterior, middle vertebral height, kyphotic angle, and Cobb angle between postural reduction and balloon dilation (each P > .05). The improvement on the Visual Analog Scale was notable (P < .05). Among a variety of factors, the fracture type (wedge type and biconcave type) affected both the height restoration (P = .003) and kyphotic angle reduction (P = .007). The bone cement injected volume was related to height restoration (P = .011) and kyphotic angle reduction (P = .018). CONCLUSIONS: Balloon inflation was useless for deformity correction. The deformity correction was attributed to postural reduction with cement strengthening. The most significant factors affecting deformity correction were the fracture type and bone cement injected volume.